STATUS HUKUM PRODUKSI GAWAI REPLIKA - Hardian Iskandar (Jurnal Justiciabelen, 2018)
Form of legal protection against the production of Gawai Replication in the form of preventive and repressive legal protection. The form of preventive legal protection in the form of legal protection for consumers is carried out at the time before the transaction occurs by providing consumer protection through the legislation that has been made. So that with the existence of these laws and regulations, consumers are expected to get protection before the transaction occurs, because there have been limitations and provisions that regulate transactions between consumers and businesses. While the form of legal protection is implemented through legal protection of consumers when after the transaction can be carried out through the District Court or outside the Court by the Consumer Dispute Settlement Agency based on the choice of the parties to the dispute